Methods to Capture User Information Needs: Design Principles for Open Data Intermediaries and Data Providers. (8th December 2021) - Gebka, Elisabeth; Crusoe, Jonathan; Ahlin, Karin
Data providers share open government data (OGD) to be transformed by intermediaries into products and services (solutions). OGD is believed to lead to many benefits. However, OGD is not reaching its expected level of reuse, which can come from a lack of awareness, interest to fulfil the user's needs, or novel perspectives to understand them. This paper presents a set of design principles to develop tailored mixed methods that capture activity-based information needs of users which could be satisfied by building information products based on OGD. The produced insights can help data providers and intermediaries to realign ideas of solutions to the user's information needs. The set of nine design principles are developed using design science research and are based on previous research and empirical testing. They have been implemented with two groups of users and three groups of data providers as participants of, respectively, face-to-face and digital workshops. The design principles and the produced insights were evaluated with practitioners. Implications for practice are that starting with the users' information needs can open a broader range of solutions and potential paths of OGD reuses, while following the design principles can help the practitioners cope with the fuzziness of the information needs and ideation process. For research, we propose a novel method that goes beyond the exclusive data provider-intermediary interaction to study new paths to improve the realization of OGD benefits.